2022
DOI: 10.1186/s12889-022-13561-7
|View full text |Cite
|
Sign up to set email alerts
|

Residential secondhand smoke in a densely populated urban setting: a qualitative exploration of psychosocial impacts, views and experiences

Abstract: Background People remain exposed to secondhand smoke, a serious health hazard, inside their home as households face challenges in setting no-smoking rules or are exposed to secondhand smoke drifting in from neighbouring homes. This study explores the psychosocial impacts, views, and experiences with residential secondhand smoke in a densely populated urban setting.  Methods In-depth online or face to face interviews with 18 key informants who had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
0
2
0
1
Order By: Relevance
“…O uso do tabaco, principalmente na adolescência, tornou-se um problema mundial de saúde pública relacionado a mais de 200 tipos de doenças, como as doenças crônicas, dentre elas a hipertensão arterial, diabetes mellitus e as doenças respiratórias. A fumaça produzida pelo uso do tabaco, como no caso do cigarro tradicional, pode gerar repercussões para aqueles que são fumantes ativos e passivos, como câncer de pulmão, câncer de mama, asma, estresse, dores de cabeça, sintomas respiratórios, dores no peito e dificuldades para respirar (15) .…”
Section: Aspectos éTicosunclassified
“…O uso do tabaco, principalmente na adolescência, tornou-se um problema mundial de saúde pública relacionado a mais de 200 tipos de doenças, como as doenças crônicas, dentre elas a hipertensão arterial, diabetes mellitus e as doenças respiratórias. A fumaça produzida pelo uso do tabaco, como no caso do cigarro tradicional, pode gerar repercussões para aqueles que são fumantes ativos e passivos, como câncer de pulmão, câncer de mama, asma, estresse, dores de cabeça, sintomas respiratórios, dores no peito e dificuldades para respirar (15) .…”
Section: Aspectos éTicosunclassified
“… 8 Several studies have indicated that SHS is closely associated with a psychosocial environment that increases the risk of depression. 8 10 Non-smokers who are chronically and persistently exposed to SHS may have a lower overall socioeconomic status and a higher likelihood of being in stressful environments than those without SHS exposure. 11 SHS in women, who have a higher proportion of low socioeconomic status than men, is associated with higher levels of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has emerged to reveal the association between passive smoking and lung cancer, invasive meningococcal disease, and allergic disease ( 20 ). Singaporeans, both young and old, are at high risk for passive smoking due to proximity between multi-unit residential areas which are inhabited by 80% of Singaporeans, allowing for ETS to drift into neighboring homes ( 21 ). In accordance with the Global Burden of Disease 2019 study, the annual mortality rates attributed to second-hand smoke exposure in Singapore was estimated at 261 in 2015, increasing steadily to 296 in 2019 ( 22 ).…”
Section: Introductionmentioning
confidence: 99%